Efektivitas Water Chiller Menggunakan Metode Overall Equipment Effectiveness pada Industri Farmasi - R Nurafijah; Z Rafandra; O Supriyadi; O. A. Rojak; M. I. Muzaky (Jurnal MESIL (Mesin Elektro Sipil), 2026)
In pharmaceutical manufacturing, the chiller system plays a crucial role in maintaining environmental and equipment temperatures in compliance with CPOB and BPOM standards. At PT. X, frequent downtime and recurring failures of the water chiller units have disrupted production stability and reduced operational efficiency. This study aims to evaluate the performance effectiveness of water chillers using the Overall Equipment Effectiveness (OEE) method, focusing on three core indicators: Availability, Performance Efficiency, and Quality Rate. The research was conducted on three chiller units over a three-month observation period from September to November 2024. Data were analyzed through field observations, performance calculations, and failure analysis using the Six Big Losses and Fishbone Diagram methods. The results show that only one unit achieved the global OEE standard of 85%, while others fell below due to lower quality performance and excessive reduced-speed losses. The main causes of performance decline were identified as inadequate preventive maintenance, inconsistent operating procedures, and limited operator training. Based on these findings, the study recommends implementing structured maintenance schedules, routine inspections, and operator development programs to enhance overall chiller reliability, increase equipment effectiveness, and ensure production continuity within the pharmaceutical environment.